The impact of the EVFTA on responsible business practices in Vietnam: implementation and challenges - Chien Dinh Thi; Dung Ho Xuan; Son Luong Minh (TalTech Journal of European Studies, 2025)
The EU-Vietnam Free Trade Agreement (EVFTA) not only promotes trade liberalization, but also emphasizes the importance of sustainable development through the adoption of responsible business practices (RBP). This article examines the impact of the EVFTA on promoting RBP in Vietnam, with a focus on labor-intensive industries, such as those of textile, footwear, printing and wood processing. By analyzing data from the Vietnam Chamber of Commerce and Industry (VCCI) surveys, Better Work (BW) reports and case studies of two enterprises, this study identifies the key drivers and obstacles in implementing RBP. The findings highlight the dual role of the EVFTA in accelerating regulatory improvements and imposing market-driven pressure for compliance. However, challenges remain in the form of legal framework gaps, enforcement limitations and financial burdens on small and medium-sized enterprises (SMEs). The study concludes with policy recommendations aimed at enhancing the effectiveness of the RBP, thereby ensuring that Vietnam not only meets its international commitments but also achieves sustainable economic development.